STRATEGI PENGELOLA PERPUSTAKAAN DALAM MENINGKATKAN MINAT MEMBACA SISWA DI SMA NEGERI SUMATERA SELATAN - Roihan, Muhammad Roihan Arda Pratama; Bety, Bety; Rusmiatiningsih, Rusmiatiningsih (Program Studi Ilmu Perpustakaan dan Informasi, Universitas Islam Nusantara, 2024)
Strategy of library managers in increasing students' reading interest in South Sumatra State High Schools. This research aims to find out how students' reading interest is, and what the library management's strategy is in increasing students' reading interest in South Sumatra State High Schools. This research uses a qualitative descriptive research type, where the data collection techniques used are observation, in-depth interviews with 13 informants, and documentation. The data analysis technique used is by reducing data, presenting data, and drawing conclusions. The results of the research show that the reading interest of students at South Sumatra State High School is considered good in terms of the reading intensity and quantity of reading of South Sumatra State High School students and the strategies carried out by the library management of South Sumatra State High School in increasing students' interest in reading consisting of: reading 15 minutes before studying, studying in the library, library Competition, article writing competition, and Vlog making competion. Keyword: library manager, strategy, interest in reading ABSTRAK Strategi pengelola perpustakaan dalam meningkatkan minat membaca siswa di SMA Negeri Sumatera Selatan. Penelitian ini bertujuan untuk mengetahui bagaimana minat baca siswa, dan bagaimana strategi pengelola perpustakaan dalam meningkatkan minat baca siswa di SMA Negeri Sumatera Selatan. Penelitian ini menggunakan jenis penelitian deskriptif kualitatif, dimana teknik pengumpulan data yang dilakukan yaitu observasi, wawancara mendalam dengan 13 informan, dan dokumentasi. Teknik analisis data yang dilakukan yaitu dengan mereduksi data, menyajikan data, dan menarik kesimpulan. Hasil penelitian menunjukan bahwa minat baca siswa di SMA Negeri Sumatera Selatan sudah tergolong baik dilihat dari intensitas bacaan dan kuantitas bacaan siswa SMA Negeri Sumatera Selatan dan strategi yang dilakukan pengelola perpustakaan SMA Negeri Sumatera Selatan dalam meningkatkan minat baca siswa terdiri dari: membaca 15 menit sebelum belajar, belajar di perpustakaan, lomba perpustakaan, lomba membuat artikel, dan lomba membuat vlog.